The Effectiveness of Weighing Scale Calibration/Recalibration in Consumer - Abdul Kadir Latuconsina; Fahrudin Ramly; Dientje Rumerung (Univiversitas Dr. Djar Wattiheluw, 2024)
The activity of calibration/re-calibration has influenced consumer behavior in purchasing goods. The purpose of this study is to understand consumer behavior in determining purchases from sellers whose measuring, weighing, and related equipment (UTTP) have been calibrated/re-calibrated, and its implications on seller income. This research uses a qualitative method. The data used is primary data obtained by conducting interviews with 50 consumers and 50 sellers using incidental sampling techniques. Data and information obtained were analyzed qualitatively through descriptive analysis and narrative. The research results indicate that consumers tend to choose sellers whose UTTP equipment has been calibrated/re-calibrated, except in situations of necessity, such as indebtedness or hurry. This has an impact on increasing seller income than before calibration/re-calibration.